Bilateral synchronous ovarian tumours: an uncommon case and review of the literature - Günakan, Emre; Tohma, Yusuf A.; Haberal, Asuman N.; Ayhan, Ali (Menopause Review/Przegląd Menopauzalny, 2018)
Synchronous ovarian tumours are rare. Management of these patients can differ from that of patients with uniform tumours. We present a case of synchronous epithelial ovarian cancer and malignant mixed Müllerian tumour in different ovaries, its follow-up and management until death. To our knowledge this is the second case in the English literature to date. A 61-year-old woman with bilateral adnexal masses underwent complete debulking surgery for ovarian cancer. The final pathology was reported as malignant mixed Müllerian tumour in the right ovary with intact borders and stage 2 grade 3 serous carcinoma in the left ovary. She had a 17-month disease-free interval after 6 cycles of paclitaxel and carboplatin. Recurrence of malignant mixed Müllerian tumour was reported in the pathology after secondary debulking including a partial ileal resection. After 6 cycles of gemcitabine and cisplatin she had a widespread recurrence in the thorax and abdomen. The patient died of disease recurrence at the 25th month after diagnosis. Coexistence of serous and malignant mixed Müllerian tumour in different ovaries is very rare. The main treatment is complete cytoreduction followed with chemotherapy. Platinum-taxane based chemotherapy resulted in an acceptable disease-free interval in our case, but it is not standard yet. A management protocol may be developed with the increasing number of similar cases in the literature.